(1162) The Challenge of Indigenizing the African Economy (Egyptian Country Study التحدي المتمثل في تقصير الاقتصاد الأفريقي (دراسة البلد المصري) - Hanfi, Mohamed A. (معهد التخطيط القومى, 2024)
The area of Arab Republic of Egypt is about 386299 square mile (on million square kilometers). However, 4 per cent can be said to be permanently settled and cultivated). The population are thron in a narrow valley some 2 to 20 miles wide cut by the river Nile and Delta gion. In addition there is a new valley consists of a deries of depressions in the western desert and which exteds parallel to the Nile. The cultivable land in these depressions is more than three million acres. However, the agricultrual development in the new valley depends mainly on the possibilities of the underground water.